Crisis management planning of the forest products industry enterprises in the process of institutionalization in the COVID-19 pandemic - Tarık Gedik; Ahmet Bora Kırklıkçı (Turkish Journal of Forestry, 2022)
The negative aspect of the COVID-19 pandemic, whose impact in the economic field began to be felt much more especially after the third quarter of 2020, has emerged in every sector. Institutionalized businesses have been less affected by the pandemic than other businesses. With this study, it has been tried to analyze the crisis management plans of the forest products industry enterprises, which are institutionalized at a certain level or on the way to institutionalization, in the COVID-19 process. The data obtained by using individual in-depth interviews with business managers were coded, described, analyzed and interpreted in accordance with the combined qualitative research reporting criteria. According to the results obtained from fourteen different forest products industry enterprises, managers defined the need to be prepared for the crisis and stated that this preparation should be done by the top management. According to managers, the pandemic process has caused major changes in consumer behavior. The managers stated that the period caused the most loss of workforce and loss of jobs and markets (economic loss). Business managers are advised to make risk assessments, prepare contingency plans and develop crisis management models in order to minimize the effects of the COVID-19 pandemic in their businesses.